Imaging features of β-catenin-activated hepatocellular adenoma with weak β-catenin activation: A rare case report. (23rd November 2022) - Minamiguchi, Kiyoyuki; Marugami, Nagaaki; Uchiyama, Tomoko; Kusano, Hironori; Yasuda, Satoshi; Sho, Masayuki; Tanaka, Toshihiro
We report valuable imaging findings in a case of β-catenin-activated hepatocellular adenoma (β-HCA) with weak β-catenin activation. A 40 year-old female presented with a liver tumor in S8 that was incidentally detected on ultrasonography. The tumor showed marked enhancement and early venous drainage into the middle hepatic vein in the arterial phase of contrast-enhanced computed tomography (CT). The tumor revealed slight hypointensity in the hepatobiliary phase of gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid-enhanced magnetic resonance imaging (EOB-MRI). Six months after detection, the tumor had increased in size and a biopsy indicated hepatocellular carcinoma. The tumor was resected and pathologically diagnosed as β-HCA with weak β-catenin activation such as exon 3 S45 mutation and exon 7/8 mutation. Marked enhancement in the arterial phase of CT and MRI is a characteristic finding of β-HCA with weak β-catenin activation. Furthermore, the degree of β-catenin activation might determine the signal intensity of β-HCA in the hepatobiliary phase of EOB-MRI.